Spreading Depolarization Facilitates the Transition of Neuronal Burst Firing from Interictal to Ictal State. (10th August 2020) - Rathmann, Thomas; Khaleghi Ghadiri, Maryam; Stummer, Walter; Gorji, Ali
Highlights: A complex link between spreading depolarization (SD) and epileptiform burst discharges has been observed. The effect of SD on the interictal-to-ictal transitions in low-Mg 2+ model of seizure was studied in rat hippocampus. SD significantly accelerates the interictal-to-ictal transitions and facilitates development of ictaform discharges. SD may play a potential role in seizure initiation in temporal lobe epilepsy. Abstract: The transition of neuronal burst firing from the interictal to ictal state contributes to seizure initiation in human temporal lobe epilepsy. The low-Mg 2+ model of seizure is characterized by initial spontaneous interictal bursting events, which later developed into ictaform discharges. Both experimental and clinical studies point to a complex link between spreading depolarization (SD) and epileptiform field potentials (EFP), including SD-induced epileptic seizures. To investigate the mechanism of SD and EFP interactions, the effect of SD on the transition of interictal to ictal state in low-Mg 2+ model of seizure was studied in the rat hippocampus in vitro . After the appearance of interictal activities, SD was elicited by local application of KCl. SD significantly increased the amplitude and duration of action potentials and after-hyperpolarization, and hyperpolarized the membrane potential. Furthermore, SD significantly increased the duration of interictal activities and the threshold potentials of interictal activities. In addition, SD significantly accelerated the transition from interictal to ictal state compared to the control tissues. Ictal activities after induction of SD exhibited a significantly longer duration. This study revealed that SD accelerates interictal-to-ictal transitions and facilitates development of ictaform discharges, possibly via the enhancement of neural synchronization, and points to the potential role of SD in seizure initiation.